About the impulse to flee in No hay nadie allá afuera de Alberto Fuguet - Marcelo Ignacio Navarro Morales; Carla Llamunao (Estudios de Teoría Literaria, 2023)
This article analyzes the story No hay nadie allá afuera by Alberto Fuguet, from the perspective of Peter Sloterdijk's philosophy on individualism in contemporary societies. Through this story, we witness the dismantling of the myth of the modern subject, capable of living outside the identifications of class and nation, and of vindicating his individuality to the last consequences. The analysis of the story confirms that the protagonist's impulse to flee comes from the appropriation of the codes and languages of the American audiovisual industry, on the one hand, and from the spatial operations that the foamy city restricts, prohibits and/or suggests, on the other; which empties the subject, causing him to lean toward cynicism and the suicide.